FMRI analysis of contrast polarity processing in face-selective cortex in humans and monkeys - Yue, Xiaomin (2013)
Recognition is strongly impaired when the normal contrast polarity of faces is reversed. For instance, otherwise-familiar faces become very difficult to recognize when viewed as photographic negatives. Here, we used fMRI to demonstrate related properties in visual cortex: 1) fMRI responses in the human Fusiform Face Area (FFA) decreased strongly (26%) to contrast-reversed faces across a wide range of contrast levels (5.3-100% RMS contrast), in all subjects tested. In a whole brain analysis, this contrast polarity bias was largely confined to the Fusiform Face Area (FFA; p < 0.0001), with possible involvement of a left occipital face-selective region. 2) It is known that reversing facial contrast affects three image properties in parallel (absorbance, shading, and specular reflection). Here, comparison of FFA responses to those in V1 suggests that the contrast polarity bias is produced in FFA only when all three component properties were reversed simultaneously, which suggests a prominent non-linearity in FFA processing. 3) Across a wide range (180°) of illumination source angles, 3D face shapes without texture produced response constancy in FFA, without a contrast polarity bias. 4) Consistent with psychophysics, analogous fMRI biases for normal contrast polarity were not produced by non-face objects, with image statistics similar to the face stimuli. 5) Using fMRI, we also demonstrated a contrast polarity bias in awake behaving macaque monkeys, in the cortical region considered homologous to human FFA. Thus common cortical mechanisms may underlie facial contrast processing across ~ 25 million years of primate evolution.